A Network Pharmacology-Based Approach for Exploring Key Active Compounds and Pharmacological Mechanisms of Tangshen Formula for Treatment of Diabetic Nephropathy - Weie Zhou; Xuefeng Zhou; Yuan Zhang; Yuyang Wang; Wenjie Wu; Haojun Zhang; Tingting Zhao; Liang Peng; Hailing Zhao; Ping Li (Journal of Diabetes Research)
Diabetic nephropathy (DN) is one of the common and severe microvascular complications of diabetes mellitus (DM). The occurrence and development of DN are related to multiple factors in the human body, which makes DN a complex disease, and the pathogeneses of DN have not yet been fully illustrated. Furthermore, DN lacks effective drugs for treatment nowadays. Chinese herbal medicine (CHM) often shows the feature of multicomponents, multitargets, multipathways, and synergistic effects and shows a promising source of new therapeutic drugs for DN. As a CHM, Tangshen Formula (TSF) was used to treat DN patients in China. However, its bioactive compounds and holistic pharmacological mechanisms on DN are both unclear. A network pharmacology approach was firstly applied to explore multiple active compounds and multiple key pharmacological mechanisms for TSF treating DN by drug-targeted interaction databases, herb-compound-target network, protein-protein interaction network, compound-target-pathway network, and analysis methods. And the results showed that TSF have the characteristic of multicomponents, multitargets, multipathways, and synergistic effects for treating DN. The quercetin, naringenin, kaempferol, and isorhamnetin as key active compounds and the PI3K-Akt signaling pathway, TNF signaling pathway, nonalcoholic fatty liver disease (NAFLD), focal adhesion, rap1 signaling pathway, T cell receptor signaling pathway, MAPK signaling pathway, and insulin resistance as the key molecular mechanisms play important roles in TSF treating DN. Moreover, quercetin, naringenin, kaempferol, and isorhamnetin were successfully detected in TSF by the UHPLC-MS/MS analysis method. And their concentrations were 0.224, 8.295, 0.0564, and 0.0879 mg·kg-1, respectively. The present findings not only provide new insights for a deeper understanding of the constituent basis and pharmacology of TSF but also provide guidance for further pharmacological studies on TSF.